Penerapan Model Pembelajaran Saintifik Tipe Discovery Learning untuk Meningkatkan Motivasi dan Hasil Belajar Matematika Peserta Didik Kelas XI IPS 1 MAN 2 Kota Padang - Desmulyani Desmulyani (Journal of Education and Culture (JEC), 2022)
This study aims firstly to explain the increase students' learning motivation, secondly to find out the increase students learning outcomes after learning mathematics using a scientific model with discovery learning type. The research was conducted at MAN 2 Kota Padang  Jalan Gajah Mada no. 100, Padang Utara district. The subjects of this study were students of class XI IPS 1 Man 2 Kota Padang  in the second semester of the 2019/2020 academic year, consisted of 35 people with 19 males and 16 females.The type of this research is Classroom Action Research (CAR) which was carried out in two cycles, each cycle consists of two meetings. The results of the study is first, the implementation of learning using a scientific model with discovery learning type, in the first cycle, it is worth 66.7 and in the second cycle it is 83.3 with a good category; second, questionnaire data about students' mathematics learning motivation, in cycle, I it is worth 78.7 and in cycle II, it is worth 85.2. It means there is an increase of 6.5 points; third, data on students' mathematics learning outcomes, in cycle I obtained an average value of 70 ,8 with classical completeness 51.4% and in the cycle II,  the average value is 81.9 with classical completeness 80%, means that there is an increase in learning outcomes of 11.1 points.In conclusion, the discovery learning model can increase the motivation and mathematics learning outcomes of students in class XI IPS 1 MAN 2 Kota Padang.